Cross-resistance in DDT-resistant strains of Culex quinquefasciatus say (Diptera culicidae) - Paragas, Bonifacia P.
A high degree of selective pressure placed by modern organic insecticides upon arthropod population has caused the development of many cases of marked resistance. The appearance of resistance is so dramatic, and a threat to adequate control, that the underlying mechanisms are being thoroughly studied. The mechanism of resistance in insect, in general, cannot be explained in terms of a single factor common to all resistant species. DDT-resistance, particularly, in Culex quinquefasciatus Say (= C.p. fatigans Wiedemann) is not specifically explained by dehydrochlorination mechanism alone, unlike in Aedes aegypti where the DDT-resistance mechanism are ascertained. Owing to the complexity in the nature of DDT-resistance in this specie, more studies are required to elucidate this phenomenon. Laboratory tests were carried out in 17 different insecticides and with insecticide synergists combination to a susceptible and three resistant strains (London-S, Klongton, Ranong and London-R), to establish the cross-resistance pattern in these strains and to obtain further information on the types of resistance mechanism present in them, by taking into consideration the effects of synergists. In addition, studies were done to determine the most promising insecticide and the feasible insecticide-synergist combination to be utilized in the control of DDT-resistant strains of C. quinquefasciatus. Klongton and Ranong strains similarly showed high resistance to DDT (X2500and X4300, respectively) and moderate cross-resistance to Prolan, X26 for the former and X21 for the later. A moderate cross-resistance to DDD, with resistance level of X17 and X16 from two resistant strains was noted. There were low levels of tolerance to some non-dehydrochloninable DDT analogues and to other groups of copound. These findings indicate the presence of alternative mechanism aside from dehydrochlorination mechanism. London-R strain exhibited a high resistance to DDT (X5000) and moderate cross-resistanceto DDD (X20.70). No cross resistance to Prolan or Bulan and other biodegradable analogues. As to other compounds tested, low tolerance levels were observed (X1 to X2). This indicate that dehydrochlorination is a major mechanism for DDT-resistancein this strain. Toxicity tests showed that among the tested compounds, Cislin (a pyrethroid) was the most potent withLC 50 value of 0.00009 ppm. for the susceptible strain. Altosid and Dimilin with LC 50 value of 0.00055 ppm. and 0.00026 ppm., respectively, were found to be highly toxic to susceptible strain. The toxicity of these three compaounds were similar for the 3 resistant strains. No cross-resistance was noted in theseinsecticides thus manifesting their usefulness in the immediate future, for vector control. ?.BONIFACIA P. PARAGAS.